2006
DOI: 10.1021/bp050326h
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the pfl Gene and Resulting Metabolite Flux Distribution in nuo and ackA-pta E. coli Mutant Strains

Abstract: Our laboratory previously studied the interaction between nuo and the acetate-producing pathway encoded by ackA-pta in Escherichia coli. We examined metabolic patterns, particularly the ethanol and acetate production rates, of several mutant strains grown under anaerobic growth conditions. Since the pyruvate formate-lyase (PFL) pathway is the major route for acetyl-CoA and formate production under anaerobic conditions, we examined the effects of nuo and ackA/pta mutations on the expression of pyruvate formate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In this study, we analyzed the underlying mechanism of the diauxic growth in the pta mutant. It is well known that pyruvate and 2‐oxoglutarate accumulate in culture media of acetate overflow‐deficient mutants [21–24]. It was also recently found that some amino acids were actively utilized even in the presence of glucose [25] and that the resultant intracellular accumulation of pyruvate and oxaloacetate reduced glucose uptake and increased acetate overflow [26].…”
mentioning
confidence: 99%
“…In this study, we analyzed the underlying mechanism of the diauxic growth in the pta mutant. It is well known that pyruvate and 2‐oxoglutarate accumulate in culture media of acetate overflow‐deficient mutants [21–24]. It was also recently found that some amino acids were actively utilized even in the presence of glucose [25] and that the resultant intracellular accumulation of pyruvate and oxaloacetate reduced glucose uptake and increased acetate overflow [26].…”
mentioning
confidence: 99%